An Empirical Characterization of Redistribution Shocks and Output Dynamics - Klemens Hauzenberger; Robert Stehrer (The Vienna Institute for International Economic Studies (wiiw), 2010)
What are the economic effects of redistributing one dollar from profits to labour income? We address this question for the post-World War II economies of the United States and Canada within a structural VECM procedure allowing for up to two breaks of unknown timing. In the United States the short-run spending effect on growth, set in motion by higher labour income, is strong enough to make such a redistribution an attractive, maybe provocative, policy alternative. Across the border in Canada, however, the negative medium-run capacity effect, brought about by diminished profits, dominates the picture more or less from the beginning and output slumps considerably, a result actually suggesting a - maybe even more provocative - redistribution towards profits. We discuss several possible explanations such as the formation of expectations and the different exposure to international trade. Methodologically, we provide a novel procedure to estimate cointegrating rank and break dates jointly.
Keywords: C32; C53; E12; E25; 330; redistribution; structural VECM; joint estimation of cointegrating rank and multiple break dates